2021
DOI: 10.1016/j.jaad.2020.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Treatment practices for psoriasis and how they are changing

Abstract: ongoing and evolving regulations and practice adaptations, 15.7 million patient visits and $3.5 billion in practice revenue could be lost through 2020.Practices most frequently identified patient social distancing (67.1%; 95% CI, 63.8%-70.3%), patient COVID-19 concerns (67.2%; 95% CI, 63.9%-70.4%), and office workflow and personal protective equipment requirements (56.3%; 95% CI, 52.9%-59.7%) as significant challenges to recovery. Among those who responded, 1% specifically noted they retired from dermatology d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
(2 reference statements)
3
7
0
Order By: Relevance
“…In addition, Muddasani et al found a stable trend in acitretin and apremilast use, while we showed an increase in apremilast use and a decrease in acitretin use. 1,2 Differences in these results are likely due to the study designs. Muddasani et al included both new and continued therapies, while we only counted therapies prescribed in newly diagnosed psoriasis patients.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, Muddasani et al found a stable trend in acitretin and apremilast use, while we showed an increase in apremilast use and a decrease in acitretin use. 1,2 Differences in these results are likely due to the study designs. Muddasani et al included both new and continued therapies, while we only counted therapies prescribed in newly diagnosed psoriasis patients.…”
mentioning
confidence: 92%
“…Despite these differences in the study populations, both analyses found increasing biologics use in the treatment of patients with psoriasis, supporting the impact of biologics for psoriasis treatment. 1,2 The reasons for the upward trend in biologics use are likely multifactorial, including excellent efficacy and convenient dosing schedules. 3 There were several key differences in our findings compared to those of Muddasani et al 1 First, Muddasani et al found a stable trend in the phototherapy use in all patients with psoriasis while we observed a decline in phototherapy use in newly diagnosed patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] The main symptoms include red papules, erythema, and silver-white scales. [4][5][6] So far, the cause of psoriasis is not clear. [7] According to related research, there are many inducing factors, including heredity, infection, abnormal immune function, abnormal metabolic function, abnormal endocrine function, and so on.…”
Section: Introductionmentioning
confidence: 99%